2022
DOI: 10.1039/d2ra01398c
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun porous poly(3-hydroxybutyrate-co-4-hydroxybutyrate)/lecithin scaffold for bone tissue engineering

Abstract: An electrospun P34HB scaffold was prepared and coated with lecithin. As a scaffold for bone tissue engineering, the P34HB/lec scaffold could promote proliferation and osteogenesis of BMSCs in vitro, and also accelerate bone regeneration in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…In addition, electrospun porous nanofibers have also attracted great attention in tissue engineering. Liu et al [ 166 ] prepared a porous poly (3-hydroxybutyrate co-4-hydroxybutyrate) (P34HB) scaffold covered with lecithin that self-assembled on the surface of a scaffold by electrospinning technology. Porous scaffolds provided mesenchymal stem cells from bone marrow protection and sufficient three-dimensional space for cell proliferation.…”
Section: Applications Of Electrospun Porous Nanofibersmentioning
confidence: 99%
“…In addition, electrospun porous nanofibers have also attracted great attention in tissue engineering. Liu et al [ 166 ] prepared a porous poly (3-hydroxybutyrate co-4-hydroxybutyrate) (P34HB) scaffold covered with lecithin that self-assembled on the surface of a scaffold by electrospinning technology. Porous scaffolds provided mesenchymal stem cells from bone marrow protection and sufficient three-dimensional space for cell proliferation.…”
Section: Applications Of Electrospun Porous Nanofibersmentioning
confidence: 99%
“…It was established [ 19 ] that the coating of scaffolds made of the Mg 2 SiO 4 –CuFe 2 O 4 nanocomposite and a layer of PHB increases cell viability, alkaline phosphatase activity, and scaffold mineralization when osteoblast-like cells are cultivated on it. It was also found [ 34 ] that fibrous scaffolds made of the P4HB copolymer by electrospinning significantly facilitate attachment and growth of MSCs isolated from rat bone marrow. The scratch model (mechanical removal of cells on the scaffold surface in the form of a strip of a specified width) also demonstrated that P4HB-fibre scaffolds support MSC migration.…”
Section: Scaffolds From Poly(3-hydroxybutyrate) and Its Copolymers Fo...mentioning
confidence: 99%
“…In another study [ 34 ], scientists used a bilateral critical bone defect of the parietal bone. The diameter of each defect was 5 mm; one of the defects was covered with a fibrous scaffold made of the P4HB copolymer.…”
Section: Scaffolds Based On Poly(3-hydroxybutyrate) and Its Copolymer...mentioning
confidence: 99%